A two-step model for creative teaching in higher education - Nathalie Sheridan (Association for Learning Development in Higher Education (ALDinHE), 2020)
This paper provides examples of practice demonstrating some underlying principles of translating creative and active pedagogies from school into a higher education context, using a simple two-step model and the concept of creative learning and teaching (Jeffrey, 2006). Since working in higher education, I sought to translate the principles of creative learning and teaching (Jeffrey, 2006) into my praxis. This exercise became particularly prudent when moving into academic development, trying to convey the successful principles underlying my pedagogy to colleagues on the Masters in Academic Practice. The paper will discuss a two-step model I developed: de-contextualizing and then re-contextualizing sometimes complex and intangible learning content to make it more accessible for learners. This will be exemplified by two teaching cases and evidenced with data I collected during my own Postgraduate Certificate in Learning and Teaching in Higher Education, demonstrating how the approach improved student performance and the overall quality of their academic work. These principles could be easily translated into different disciplinary contexts, with different groups of students.